Titanium disulfide-doped spherical hard carbon material as well as preparation method and application thereof
By adding titanium disulfide to hard carbon and adopting hydrothermal reaction and high-temperature carbonization processes, the problem of titanium disulfide deformation and low compaction density of sodium ion battery negative electrode material is solved, and a higher cycle life and specific capacity is achieved.
Patent Information
- Application Number
- CN202311797294.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2024-12-24
AI Technical Summary
The existing sodium ion battery negative electrode material, titanium disulfide, deforms greatly during the sodium ion embedding and disengagement process, resulting in a short cycle life and low compaction density of hard carbon materials affects the volume specific capacity.
Titanium disulfide is incorporated into hard carbon to prepare spherical hard carbon materials through hydrothermal reactions, and the pre-carbonization and high-temperature carbonization processes of acids or salts are used to improve the compaction density and pore structure of the carbon balls, and inhibit the deformation of titanium disulfide.
It improves the cycle life and specific capacity of sodium ion batteries, enhances the first charge and discharge efficiency, and extends the cycle performance of the battery.
Smart Images

Figure CN119181779A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a spherical hard carbon material doped with titanium disulfide and a preparation method and application thereof. Background Art
[0002] Sodium-ion batteries and lithium-ion batteries are both secondary batteries. They work on similar principles and rely mainly on the movement of alkali metal ions between the positive and negative electrodes. Compared with lithium-ion batteries, sodium-ion batteries have the advantages of a wide range of raw material sources, low cost, excellent high and low temperature performance, no over-discharge, relatively stable chemical properties, and high safety, and have good commercial prospects.
[0003] Titanium disulfide was first used in sodium-ion batteries in 1976. It has a high theoretical sodium insertion capacity of 957 mAh / g. However, when used as a negative electrode, it undergoes large deformation as sodium ions are inserted and removed, resulting in a short cycle life. Hard carbon is currently the most promising negative electrode material for sodium-ion batteries. It has the advantages of a wide range of precursor sources, large interlayer spacing, a large number of corresponding sodium ion insertion and removal active sites, and better rate and cycle performance than other sodium-ion battery negative electrodes. Biomass hard carbon is currently the most widely studied hard carbon. It has the advantages of a wide range of raw material sources, low raw material prices, and high mass specific capacity. However, biomass hard carbon generally has the disadvantage of low compaction density, which affects the volume specific capacity. Summary of the invention
[0004] In order to overcome the problems in the prior art, the present invention adds titanium disulfide to hard carbon, and uses the high theoretical specific capacity of titanium disulfide to improve the overall specific capacity. At the same time, it has an average specific capacity of 2.0g / cm2 relative to hard carbon. 3 Higher density 3.5g / cm 3 , increasing the compaction density of the carbon balls; the hard carbon inhibits the deformation of titanium disulfide during the absorption and desorption of sodium ions, thereby improving the cycle performance of titanium disulfide.
[0005] In order to achieve the above object, an embodiment of the present invention provides a method for preparing a spherical hard carbon material doped with titanium disulfide, comprising the following steps:
[0006] (1) mixing a water-soluble polysaccharide with water, stirring and dissolving the mixture, placing the mixture in a hydrothermal reactor, heating the mixture under sealed conditions, performing a hydrothermal reaction, filtering the mixture, and drying the mixture in an inert atmosphere to obtain carbon balls;
[0007] (2) soaking the carbon balls in an acid or salt aqueous solution to obtain a mixed solution A, drying the mixed solution A in an inert atmosphere, and then pre-carbonizing the mixed solution in an inert atmosphere to obtain porous carbon balls;
[0008] (3) stirring and mixing the porous carbon balls, titanium sulfate and water to obtain a mixed solution B, drying the mixed solution B in an inert atmosphere, and then heating and reducing the dried material by introducing a reducing gas under the protection of an inert atmosphere to obtain porous carbon balls doped with titanium disulfide;
[0009] (4) The porous carbon balls doped with titanium disulfide are heated in an inert atmosphere for high-temperature carbonization to obtain spherical hard carbon doped with titanium disulfide.
[0010] In one embodiment, in step (1), the water-soluble polysaccharide is at least one of gum arabic, lentinan, tuckahoe polysaccharide, and inulin; the filling rate of the hydrothermal reactor is 80%; the hydrothermal reaction temperature is 200-350°C, and the reaction time is 24-72h.
[0011] In one embodiment, in step (2), the acid is at least one of phosphoric acid and polyphosphoric acid; the salt is at least one of zinc chloride, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and zinc dihydrogen phosphate; the concentration of the aqueous solution of the acid or salt is 10% to 80%; the pre-carbonization temperature is 450° C. to 800° C., and the pre-carbonization time is 1 to 4 hours.
[0012] In one embodiment, in step (3), the mass ratio of the porous carbon balls to titanium sulfate is 100:5 to 100:15; the reducing gas is hydrogen, and the volume fraction of hydrogen is 25% to 75%; the temperature of the heating reduction process is 250 to 350°C, and the time is 1 to 4 hours.
[0013] In one embodiment, in step (4), the high temperature carbonization temperature is 1200° C. to 1600° C., and the time is 2 to 6 hours.
[0014] In one of the embodiments, the temperature of the drying process is 100-150° C., and the drying time is 12-24 hours.
[0015] The embodiment of the present invention further provides a spherical hard carbon material doped with titanium disulfide. The spherical hard carbon material doped with titanium disulfide is obtained by the above-mentioned preparation method.
[0016] In one embodiment, the spherical hard carbon material doped with titanium disulfide includes the following technical features:
[0017] The spherical hard carbon material doped with titanium disulfide has a void structure inside, and the pore capacity is 0.05 to 0.10 cc / g;
[0018] The average particle size Dv50 of the spherical hard carbon material doped with titanium disulfide is 1 to 15 μm;
[0019] The specific surface area of the spherical hard carbon material doped with titanium disulfide is 5 to 30 m 2 / g;
[0020] The compacted density of 5t powder of the spherical hard carbon material doped with titanium disulfide is 1.00-1.20g / cm 3 .
[0021] The embodiment of the present invention also provides the use of the above-mentioned spherical hard carbon material doped with titanium disulfide in negative electrode materials.
[0022] The embodiment of the present invention also provides the use of the above-mentioned spherical hard carbon material doped with titanium disulfide in a sodium ion battery.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The present invention provides a method for preparing a spherical hard carbon material doped with titanium disulfide, wherein a water-soluble polysaccharide is first subjected to a hydrothermal reaction to generate carbon balls, and then the carbon balls are etched to form pores while being pre-carbonized at high temperature using an acid and a salt, and then the porous carbon balls are immersed in a titanium sulfate solution to allow the titanium sulfate to enter the interior of the carbon balls or be adsorbed on the surface of the carbon balls, and then the +6-valent S in the titanium sulfate is reduced to -2-valent under the action of high-temperature hydrogen to generate titanium disulfide, and finally the pore size is reduced or closed under the action of high-temperature heating and carbonization to obtain the structure of titanium disulfide-doped hard carbon balls. Precursor carbon balls are obtained by hydrothermal reaction, and based on this, the spherical shape is maintained until the final product, the particle size of the carbon balls is easy to control, and the spherical structure can provide a higher compaction density, thereby improving the volume energy density of the hard carbon material. Before pre-carbonization, the carbon balls are etched with an acid or a salt, and then the surface pores are reduced and closed by high-temperature carbonization, leaving more pores inside, and because the surface pores are reduced and closed, they have a smaller specific surface area.
[0025] (2) The spherical hard carbon material doped with titanium disulfide of the present invention can be applied to sodium ion batteries. The material has a large interlayer spacing and a small deformation during the absorption and desorption of sodium ions, thereby effectively inhibiting the expansion of the titanium disulfide coated therein during the absorption and desorption of sodium ions, thereby extending the cycle life and cycle performance of the sodium ion battery. The presence of internal pores provides more sodium storage sites for the carbon spheres, improving their specific capacity, and the small specific surface area enables them to have a good initial charge and discharge efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a SEM image of the spherical hard carbon material doped with titanium disulfide provided by the present invention;
[0028] Figure 2 The charge and discharge curve of the battery corresponding to the spherical hard carbon material doped with titanium disulfide prepared in Example 1 of the present invention as the negative electrode;
[0029] Figure 3 The charge and discharge curves of the battery using the spherical hard carbon material prepared in Comparative Example 1 of the present invention as the negative electrode. DETAILED DESCRIPTION
[0030] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0031] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0032] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods. The inert atmosphere in the present invention is any one of nitrogen, helium, neon and argon, and water is deionized water or purified water.
[0033] The present invention provides a method for preparing a spherical hard carbon material doped with titanium disulfide, comprising the following steps:
[0034] (1) Mixing water-soluble polysaccharides and water, stirring and dissolving, placing in a hydrothermal reactor, pressurizing and heating under sealed conditions at a temperature of 200 to 350° C. for hydrothermal reaction for 24 to 72 hours, filtering after the reaction, and drying in an inert atmosphere to obtain carbon balls. In this step, the water-soluble polysaccharide is at least one of gum arabic, lentinan, tuckahoe polysaccharide, and inulin.
[0035] (2) Soaking the carbon balls in an aqueous solution of an acid or salt with a concentration of 10% to 80% to obtain a mixed solution A, drying the mixed solution A in an inert atmosphere, and then pre-carbonizing the mixed solution A in an inert atmosphere at a temperature of 450° C. to 800° C. for 1 to 4 hours to obtain porous carbon balls. In this step, the acid is at least one of phosphoric acid and polyphosphoric acid; and the salt is at least one of zinc chloride, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and zinc dihydrogen phosphate.
[0036] (3) The porous carbon balls and titanium sulfate are mixed in a mass ratio of 100:5 to 100:15, and water is added to stir and mix to obtain a mixed solution B, and then the mixed solution B is dried in an inert atmosphere, and then a reducing gas is introduced into the dried material under the protection of an inert atmosphere, and heated and reduced at a temperature of 250 to 350° C. for 1 to 4 hours to obtain porous carbon balls doped with titanium disulfide. The reducing gas is hydrogen, and the volume fraction of hydrogen is 25% to 75%.
[0037] (4) The porous carbon balls doped with titanium disulfide are heated in an inert atmosphere for high-temperature carbonization, specifically at a temperature of 1200° C. to 1600° C. for 2 to 6 hours to obtain spherical hard carbon doped with titanium disulfide. In order to ensure the conditions for high-temperature carbonization, the process is carried out in a tubular furnace, a box furnace or an intermediate frequency furnace.
[0038] The drying conditions in the above processes are 100-150°C and the drying time is 12-72h to ensure that the water is completely evaporated.
[0039] The present invention also provides a spherical hard carbon material doped with titanium disulfide prepared by the above preparation method, wherein the spherical hard carbon material has a spherical shape; a porous structure inside, a pore volume in the range of 0.05 to 0.10 cc / g; an average particle size Dv50 in the range of 1 to 15 μm; and a specific surface area in the range of 5 to 30 m 2 / g range; 5t powder compaction is within the range of 1.00~1.20g / cm3. This material is used as negative electrode material in sodium ion batteries, with an initial reversible capacity of more than 400mAh / g at 0.1C, an initial charging efficiency of up to 80% at 0.1C, and a capacity retention rate of up to 86% after 500 cycles at 1C rate.
[0040] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.
[0041] Example 1
[0042] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0043] (1) Place gum arabic in a hydrothermal reactor, add deionized water and stir thoroughly until dissolved, seal the hydrothermal reactor (filling rate is 75%) and heat to 250° C. for 60 h, cool naturally and filter, take the filter residue and dry it in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0044] (2) The carbon balls were soaked in a 30% deionized water solution of phosphoric acid, and then the mixture was dried in a nitrogen oven at 150°C for 48 h. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 500°C, and the temperature was kept for 2 h to obtain porous carbon balls.
[0045] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:10, deionized water is added, and after sufficient stirring, the mixture is dried in a nitrogen oven at 150°C for 48 hours. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture with a hydrogen volume ratio of 50% is introduced. The mixture is heated to 300°C and kept warm for 2 hours to obtain porous carbon balls doped with titanium disulfide.
[0046] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1400°C under the protection of nitrogen, and kept warm for 3 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0047] Example 2
[0048] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0049] (1) Place gum arabic in a hydrothermal reactor, add deionized water and stir thoroughly until dissolved, seal the hydrothermal reactor (filling rate is 70%), heat to 250° C. for 48 h, cool naturally and filter, take the filter residue and dry it in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0050] (2) The carbon balls were soaked in a deionized water solution of 80% phosphoric acid, and then the mixture was dried in a nitrogen oven at 150°C for 48 hours. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 550°C, and the temperature was kept for 3 hours to obtain porous carbon balls.
[0051] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:15, deionized water is added, and after sufficient stirring, the mixture is dried in a nitrogen oven at 150°C for 48 hours. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture gas with a hydrogen volume ratio of 50% is introduced. The mixture is heated to 300°C and kept warm for 3 hours to obtain porous carbon balls doped with titanium disulfide.
[0052] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1600°C under the protection of nitrogen, and kept warm for 4 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0053] Example 3
[0054] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0055] (1) Place gum arabic in a hydrothermal reactor, add deionized water and stir thoroughly until dissolved, seal the hydrothermal reactor (filling rate is 80%) and heat to 200° C. for 24 h, cool naturally and filter, take the filter residue and dry it in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0056] (2) The carbon balls were soaked in a 30% zinc chloride deionized water solution, and then the mixture was dried in a nitrogen oven at 150°C for 48 hours. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 800°C, and the temperature was kept for 3 hours to obtain porous carbon balls.
[0057] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:10, deionized water is added, and after sufficient stirring, the mixture is dried in a nitrogen oven at 150°C for 48 hours. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture gas with a hydrogen volume ratio of 25% is introduced. The mixture is heated to 300°C and kept warm for 3 hours to obtain porous carbon balls doped with titanium disulfide.
[0058] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1200°C under the protection of nitrogen, and kept warm for 4 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0059] Example 4
[0060] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0061] (1) Place gum arabic in a hydrothermal reactor, add deionized water and stir thoroughly until dissolved, seal the hydrothermal reactor (filling rate is 70%) and heat to 300° C. for 24 h, cool naturally and filter, take the filter residue and dry it in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0062] (2) The carbon balls were immersed in a deionized water solution containing 30% diammonium hydrogen phosphate, and then the mixture was dried in a nitrogen oven at 100°C for 72 hours. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 500°C, and the temperature was kept for 4 hours to obtain porous carbon balls.
[0063] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:10, deionized water is added, and after sufficient stirring, the mixture is dried in a nitrogen oven at 150°C for 48 hours. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture gas with a hydrogen volume ratio of 50% is introduced. The mixture is heated to 350°C and kept warm for 2 hours to obtain porous carbon balls doped with titanium disulfide.
[0064] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1400°C under the protection of nitrogen, and kept warm for 6 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0065] Example 5
[0066] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0067] (1) Place Lentinan in a hydrothermal reactor, add deionized water and stir thoroughly until dissolved, seal the hydrothermal reactor (filling rate is 80%) and heat to 250°C for 72 hours, cool naturally and filter, take the filter residue and dry it in a nitrogen oven at 150°C for 12 hours to obtain carbon balls.
[0068] (2) The carbon balls were immersed in a deionized water solution containing 40% zinc dihydrogen phosphate, and then the mixture was dried in a nitrogen oven at 100°C for 72 hours. After cooling to room temperature, it was placed in a CVD furnace, helium was introduced, the temperature was raised to 550°C, and the temperature was kept for 3 hours to obtain porous carbon balls.
[0069] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:15, deionized water is added, and after sufficient stirring, the mixture is dried in a nitrogen oven at 150°C for 48 hours. The dried carbon balls are placed in a CVD furnace, and a mixture of helium and hydrogen with a hydrogen volume ratio of 50% is introduced. The mixture is heated to 250°C and kept warm for 4 hours to obtain porous carbon balls doped with titanium disulfide.
[0070] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1300°C under the protection of helium, and kept warm for 2 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0071] Example 6
[0072] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0073] (1) Place Lentinan in a hydrothermal reactor, add deionized water and stir thoroughly until dissolved, seal the hydrothermal reactor (filling rate is 75%) and heat to 300°C for 60 hours, cool naturally and filter, take the filter residue and dry it in a nitrogen oven at 150°C for 12 hours to obtain carbon balls.
[0074] (2) The carbon balls were immersed in a deionized water solution containing 50% polyphosphoric acid, and then the mixture was dried in a nitrogen oven at 100°C for 72 h. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 650°C, and the temperature was kept for 2 h to obtain porous carbon balls.
[0075] (3) Porous carbon balls and titanium sulfate are placed in a mixer in a mass ratio of 100:10, deionized water is added, and the mixture is dried in a nitrogen oven at 150°C for 48 hours after being fully stirred. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture gas with a hydrogen volume ratio of 50% is introduced, heated to 250°C, and kept warm for 4 hours to obtain porous carbon balls doped with titanium disulfide.
[0076] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1200°C under the protection of nitrogen, and kept warm for 3 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0077] Example 7
[0078] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0079] (1) Place Poria cocos polysaccharide in a hydrothermal reactor, add deionized water and stir thoroughly until dissolved, seal the hydrothermal reactor (filling rate is 70%) and heat to 350° C. for 72 h, cool naturally and filter, take the filter residue and dry it in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0080] (2) The carbon balls were immersed in a deionized water solution containing 30% diammonium dihydrogen phosphate, and then the mixture was dried in a nitrogen oven at 100°C for 72 h. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 500°C, and the temperature was kept for 3 h to obtain porous carbon balls.
[0081] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:5, deionized water is added, and the mixture is dried in a nitrogen oven at 150°C for 48 hours after being fully stirred. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture with a hydrogen volume ratio of 75% is introduced, heated to 300°C, and kept warm for 1 hour to obtain porous carbon balls doped with titanium disulfide.
[0082] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1400°C under the protection of nitrogen, and kept warm for 6 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0083] Example 8
[0084] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0085] (1) Place Poria cocos polysaccharide in a hydrothermal reactor, add deionized water and stir thoroughly until dissolved, seal the hydrothermal reactor (filling rate is 80%) and heat to 250° C. for 72 h, cool naturally and filter, take the filter residue and dry it in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0086] (2) The carbon balls were immersed in a deionized water solution containing 40% phosphoric acid, and then the mixture was dried in a nitrogen oven at 150°C for 48 h. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 450°C, and the temperature was kept for 3 h to obtain porous carbon balls.
[0087] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:10, deionized water is added, and after sufficient stirring, the mixture is dried in a nitrogen oven at 150°C for 48 hours. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture with a hydrogen volume ratio of 50% is introduced. The mixture is heated to 300°C and kept warm for 2 hours to obtain porous carbon balls doped with titanium disulfide.
[0088] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1500°C under the protection of nitrogen, and kept warm for 2 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0089] Example 9
[0090] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0091] (1) Inulin was placed in a hydrothermal reactor, deionized water was added and stirred until dissolved, the hydrothermal reactor was sealed (filling rate was 80%) and heated to 300° C. for 36 h, and filtered after natural cooling. The filter residue was dried in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0092] (2) The carbon balls were soaked in a deionized water solution containing 10% phosphoric acid, and then the mixture was dried in a nitrogen oven at 150°C for 48 hours. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 650°C, and the temperature was kept for 3 hours to obtain porous carbon balls.
[0093] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:15, deionized water is added, and after sufficient stirring, the mixture is dried in a nitrogen oven at 150°C for 48 hours. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture gas with a hydrogen volume ratio of 50% is introduced. The mixture is heated to 300°C and kept warm for 3 hours to obtain porous carbon balls doped with titanium disulfide.
[0094] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1300°C under the protection of nitrogen, and kept warm for 2 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0095] Example 10
[0096] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0097] (1) Inulin was placed in a hydrothermal reactor, deionized water was added and stirred thoroughly until dissolved, the hydrothermal reactor was sealed (filling rate was 75%) and heated to 300° C. for 48 h, and filtered after natural cooling. The filter residue was dried in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0098] (2) The carbon balls were immersed in a deionized water solution containing 40% zinc chloride, and then the mixture was dried in a nitrogen oven at 150°C for 48 h. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 750°C, and the temperature was kept for 3 h to obtain porous carbon balls.
[0099] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:10, deionized water is added, and the mixture is dried in a nitrogen oven at 150°C for 48 hours after being fully stirred. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture gas with a hydrogen volume ratio of 50% is introduced. The mixture is heated to 250°C and kept warm for 3 hours to obtain porous carbon balls doped with titanium disulfide.
[0100] The porous carbon balls doped with titanium disulfide were placed in a box furnace, heated to 1500°C under the protection of nitrogen, and kept warm for 4 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0101] Embodiment 11
[0102] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0103] (1) Inulin was placed in a hydrothermal reactor, deionized water was added and stirred thoroughly until dissolved, the hydrothermal reactor was sealed (filling rate was 70%) and heated to 350° C. for 60 h, and filtered after natural cooling. The filter residue was dried in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0104] (2) The carbon balls were immersed in a deionized water solution containing 80% phosphoric acid, and then the mixture was dried in a nitrogen oven at 150°C for 48 h. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 550°C, and the temperature was kept for 3 h to obtain porous carbon balls.
[0105] (3) Porous carbon balls and titanium sulfate are placed in a mixer at a mass ratio of 100:10, deionized water is added, and the mixture is dried in a nitrogen oven at 150°C for 48 hours after being fully stirred. The dried carbon balls are placed in a CVD furnace, and a nitrogen and hydrogen mixture gas with a hydrogen volume ratio of 50% is introduced. The mixture is heated to 250°C and kept warm for 3 hours to obtain porous carbon balls doped with titanium disulfide.
[0106] The porous carbon balls doped with titanium disulfide were placed in a box furnace, heated to 1600°C under the protection of nitrogen, and kept warm for 2 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0107] Example 12
[0108] A method for preparing a spherical hard carbon material doped with titanium disulfide comprises the following steps:
[0109] (1) Gum arabic is placed in a hydrothermal reactor, deionized water is added and stirred thoroughly until dissolved, the hydrothermal reactor is sealed (filling rate is 80%) and the temperature is raised to 300° C. for 48 h, and the mixture is filtered after natural cooling. The filter residue is dried in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0110] (2) The carbon balls were immersed in a deionized water solution containing 40% of ammonium dihydrogen phosphate, and then the mixture was dried in a nitrogen oven at 100°C for 72 hours. After cooling to room temperature, it was placed in a CVD furnace, argon gas was introduced, the temperature was raised to 550°C, and the temperature was kept for 3 hours to obtain porous carbon balls.
[0111] (3) Porous carbon balls and titanium sulfate are placed in a mixer in a mass ratio of 100:15, deionized water is added, and after sufficient stirring, the mixture is dried in a nitrogen oven at 150°C for 48 hours. The dried carbon balls are placed in a CVD furnace, and a mixture of argon and hydrogen with a hydrogen volume ratio of 75% is introduced, heated to 300°C, and kept warm for 2 hours to obtain porous carbon balls doped with titanium disulfide.
[0112] (4) The porous carbon balls doped with titanium disulfide are placed in a box furnace, heated to 1300°C under the protection of argon, and kept warm for 5 hours for high-temperature carbonization to obtain a finished spherical hard carbon material doped with titanium disulfide.
[0113] Comparative Example 1
[0114] (1) Inulin was placed in a hydrothermal reactor, deionized water was added and stirred thoroughly until dissolved, the hydrothermal reactor was sealed (filling rate was 80%) and heated to 300° C. for 48 h, and filtered after natural cooling. The filter residue was dried in a nitrogen oven at 150° C. for 12 h to obtain carbon balls.
[0115] (2) The carbon balls were immersed in a deionized water solution containing 40% zinc chloride, and then the mixture was dried in a nitrogen oven at 150°C for 48 h. After cooling to room temperature, it was placed in a CVD furnace, nitrogen was introduced, the temperature was raised to 750°C, and the temperature was kept for 3 h to obtain porous carbon balls.
[0116] (3) The porous carbon balls are placed in a box furnace, heated to 1500°C under the protection of nitrogen, and kept warm for 4 hours for high-temperature carbonization to obtain spherical hard carbon materials.
[0117] Comparative Example 2
[0118] A small amount of titanium sulfate was placed in a CVD furnace, a 50% nitrogen and hydrogen mixed gas was introduced, the mixture was heated to 300°C, kept warm for 3 hours, and cooled to room temperature to obtain titanium disulfide.
[0119] Spectral analysis
[0120] The spherical hard carbon doped with titanium disulfide obtained in the above examples was subjected to SEM analysis. Taking Example 1 as an example, its SEM image is as follows: Figure 1 The hard carbon negative electrode material prepared is a micron-sized sphere, and the uneven position on the surface is the part left or taken away by other spheres after adhesion and separation. There are no obvious holes on the surface, indicating that there are no pores remaining on the surface or the remaining pores are micropores and smaller mesopores.
[0121] Electrical performance analysis
[0122] The electrical properties of Examples 1 to 12, Comparative Examples 1 and 2, and the commercially available hard carbon product NED330 were tested as negative electrode materials.
[0123] Battery assembly: Assemble button batteries using the products prepared in the examples and comparative examples as the negative electrode, the sodium sheet as the positive electrode, the glass fiber as the separator, and sodium hexafluorophosphate as the electrolyte.
[0124] Performance test: The voltage was set at 0.01-2V, and the battery was discharged and charged at a rate of 0.1C to test the first reversible capacity and the first charging efficiency. After repeating the discharge and charge at a rate of 0.1C for 3 times, it was left to stand for 1 hour, and then the discharge and charge were repeated at a rate of 1C for 500 times to test its cycle performance. The performance test data is shown in Table 1. Taking the batteries corresponding to the negative electrode materials obtained in Example 1 and Comparative Example 1 as examples, the charge and discharge curves of the two are shown in Table 1. Figure 2 , 3 shown.
[0125] Table 1 Hard carbon material performance test data table
[0126]
[0127] It can be seen from the above data that the sodium ion hard carbon negative electrode materials prepared in each embodiment of the present invention have a higher powder compaction density on the basis of good electrical properties; and the low cycle performance of titanium disulfide is also improved due to its incorporation into hard carbon.
[0128] Comparative Example 1 uses exactly the same reaction conditions as Example 10 except that titanium disulfide is not added. Comparative Example 2 uses the titanium disulfide prepared by the method of preparing titanium disulfide in this patent as the negative electrode material for sodium ion batteries. From the comparison between Comparative Example 1 and NED330, it can be seen that the spherical shape can effectively increase the compaction density of the hard carbon material. From the comparison between Example 10 and Comparative Example 1, it can be seen that the addition of titanium disulfide increases the reversible capacity of the negative electrode material while also increasing the compaction density of the negative electrode material.
[0129] In Example 3, the hydrothermal reaction used a lower temperature and a shorter reaction time, and the carbon balls produced had a smaller particle size and were more compact during the compaction process, thereby obtaining a higher powder compaction density; however, the larger specific surface area due to the small particle size affected its first charging efficiency and also affected its first reversible capacity.
[0130] In Example 7, the hydrothermal reaction used a higher temperature and a longer reaction time, the produced carbon balls had a larger particle size, more voids during the compaction process, and less titanium disulfide was added, so the powder compaction density was lower.
[0131] From comparing Example 3 and Example 10 with other examples, it can be seen that the capacity gain brought by using phosphoric acid and its derivatives to form pores in carbon balls is better than that brought by using zinc chloride. This may be because phosphoric acid has both oxidation and dehydration effects at high temperatures, and phosphorus oxide P2O5 can act as a Lewis acid to react to form a COP association structure, so that the carbon balls obtain a large number of PO network structures and micropores, and more internal micropores are formed after the pores are closed, providing more sites for the adsorption of sodium ions; while zinc chloride only has a dehydration effect at high temperatures, and the pores created are not as good as phosphoric acid.
[0132] Depend on Figure 2 , 3 It can be seen that, compared with the charge and discharge curves of the batteries corresponding to the negative electrode materials of Example 1 and Comparative Example 1, the hard carbon doped with titanium disulfide showed a platform area at around 1.5V, which was the result of stable charging / discharging of the doped titanium disulfide at this voltage.
[0133] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.
Claims
1. A method for preparing a spherical hard carbon material doped with titanium disulfide, characterized in that: The steps include: (1) mixing a water-soluble polysaccharide with water, stirring and dissolving the mixture, placing the mixture in a hydrothermal reactor, heating the mixture under sealed conditions, performing a hydrothermal reaction, filtering the mixture, and drying the mixture in an inert atmosphere to obtain carbon balls; (2) soaking the carbon balls in an acid or salt aqueous solution to obtain a mixed solution A, drying the mixed solution A in an inert atmosphere, and then pre-carbonizing the mixed solution in an inert atmosphere to obtain porous carbon balls; (3) stirring and mixing the porous carbon balls, titanium sulfate and water to obtain a mixed solution B, drying the mixed solution B in an inert atmosphere, and then heating and reducing the dried material by introducing a reducing gas under the protection of an inert atmosphere to obtain porous carbon balls doped with titanium disulfide; (4) The porous carbon balls doped with titanium disulfide are heated in an inert atmosphere for high-temperature carbonization to obtain spherical hard carbon doped with titanium disulfide.
2. The method for preparing a spherical hard carbon material doped with titanium disulfide according to claim 1, characterized in that: In step (1), the water-soluble polysaccharide is at least one of gum arabic, lentinan, tuckahoe polysaccharide and inulin; the filling rate of the hydrothermal reactor is 70-80%; the hydrothermal reaction temperature is 200-350°C, and the reaction time is 24-72h.
3. The method for preparing a spherical hard carbon material doped with titanium disulfide according to claim 1, characterized in that: In step (2), the acid is at least one of phosphoric acid and polyphosphoric acid; the salt is at least one of zinc chloride, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and zinc dihydrogen phosphate; the concentration of the aqueous solution of the acid or salt is 10% to 80%; the pre-carbonization temperature is 450° C. to 800° C., and the pre-carbonization time is 1 to 4 hours.
4. The method for preparing a spherical hard carbon material doped with titanium disulfide according to claim 1, characterized in that: In step (3), the mass ratio of the porous carbon balls to titanium sulfate is 100:5 to 100:15; the reducing gas is hydrogen, and the volume fraction of hydrogen is 25% to 75%; the temperature of the heating reduction process is 250 to 350° C., and the time is 1 to 4 hours.
5. The method for preparing a spherical hard carbon material doped with titanium disulfide according to claim 1, characterized in that: In step (4), the high temperature carbonization temperature is 1200°C to 1600°C, and the time is 2 to 6 hours.
6. The method for preparing a spherical hard carbon material doped with titanium disulfide according to any one of claims 1 to 5, characterized in that: The temperature of the drying process is 100-150° C., and the drying time is 12-24 hours.
7. A spherical hard carbon material doped with titanium disulfide, characterized in that: The spherical hard carbon material doped with titanium disulfide is obtained by the preparation method according to any one of claims 1 to 6.
8. The spherical hard carbon material doped with titanium disulfide according to claim 7, characterized in that: The spherical hard carbon material doped with titanium disulfide includes one or more of the following technical features: The spherical hard carbon material doped with titanium disulfide has a void structure inside, and the pore capacity is 0.05 to 0.10 cc / g; The average particle size Dv50 of the spherical hard carbon material doped with titanium disulfide is 1 to 15 μm; The specific surface area of the spherical hard carbon material doped with titanium disulfide is 5 to 30 m 2 / g; The compacted density of 5t powder of the spherical hard carbon material doped with titanium disulfide is 1.00-1.20g / cm 3 .
9. Use of the spherical hard carbon material doped with titanium disulfide as claimed in any one of claims 7 and 8 in negative electrode materials.
10. Use of the spherical hard carbon material doped with titanium disulfide as claimed in any one of claims 7 and 8 in sodium ion batteries.
